2010
DOI: 10.1029/2010gc003097
|View full text |Cite
|
Sign up to set email alerts
|

Coherent pattern and timing of the carbon isotope excursion and warming during Eocene Thermal Maximum 2 as recorded in planktic and benthic foraminifera

Abstract: [1] Eocene Thermal Maximum 2 (ETM2; ∼53.7 Ma) occurred approximately 2 Myr after the PaleoceneEocene Thermal Maximum (∼55.5 Ma) and was characterized by a deep-sea warming of >3°C, associated with massive release of carbon into the ocean-atmosphere system. We performed single-specimen stable isotope analyses of the planktic foraminiferal genera Acarinina (surface dweller) and Subbotina (thermocline dweller) from Ocean Drilling Program Sites 1265, 1267, and 1263 (Walvis Ridge, SE Atlantic Ocean) and compared hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
59
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(60 citation statements)
references
References 53 publications
1
59
0
Order By: Relevance
“…The effect of temperature variations on placolith Sr/Ca values is minor during ETM2. The δ 18 O in benthic and planktonic foraminifera during ETM2 (Site 1265) shows a ∼2-4 • C increase (Stap et al, 2010a). This implies that at Walvis Ridge, 4-8 % of the 13 to 21 % Sr/Ca increase in Coccolithus and Toweius, respectively, could be attributed to temperature.…”
Section: Sr/ca-derived Primary Productivity Obtained By Ion Probementioning
confidence: 87%
“…The effect of temperature variations on placolith Sr/Ca values is minor during ETM2. The δ 18 O in benthic and planktonic foraminifera during ETM2 (Site 1265) shows a ∼2-4 • C increase (Stap et al, 2010a). This implies that at Walvis Ridge, 4-8 % of the 13 to 21 % Sr/Ca increase in Coccolithus and Toweius, respectively, could be attributed to temperature.…”
Section: Sr/ca-derived Primary Productivity Obtained By Ion Probementioning
confidence: 87%
“…There is also a growing appreciation that the PETM is only the most prominent of a series of "hyperthermal" events that occurred during long-term deep-ocean warming of the early Paleogene Nicolo et al, 2007;Agnini et al, 2009;Stap et al, 2009Stap et al, , 2010Leon-Rodriguez and Dickens, 2010;Zachos et al, 2010). At least five other events, presently called ETM2/H1, H2, I1, I2, and K/X (following Cramer et al, 2003), have been identified in multiple records and follow the PETM at approximately 53.7, 53.6, 53.3, 53.2, and 52.5 Ma.…”
Section: The Gas Hydrate Dissociation Hypothesismentioning
confidence: 99%
“…Benthic foraminiferal assemblages declined in diversity with postexcursion assemblages similar to the low-diversity post-PETM ones (13)(14)(15), but without significant extinction. Carbonate dissolution occurred and the lysocline rose, but the CCD did not shoal to (or beyond) the depth of the sites in the southeast Atlantic where dissolution was complete during the PETM (16).…”
mentioning
confidence: 99%
“…Eocene Thermal Maximum 2 (ETM-2, ∼53.2 Ma) occurred about 2 million years after the PETM and provides the opportunity for a comparative study, because it is qualitatively similar to the PETM, with only about half its magnitude (13). Benthic foraminiferal assemblages declined in diversity with postexcursion assemblages similar to the low-diversity post-PETM ones (13)(14)(15), but without significant extinction.…”
mentioning
confidence: 99%